The Effect of Total Asset Turn Over, Current Ratio and Sales Growth on Return on Asset with Firm Size as a Moderating Variable (In Property and Real Estate Sub-Sector Companies Listed on the Indonesia Stock Exchange 2015-2022) - Nandia Putri, Chika; Kusumawardani, Astrin (Journal of Accounting and Finance Management, 2024)
The purpose of this study is to reveal how Total Asset Turnover, Current Ratio, and sales growth affect Return on Asset in property and real estate companies on the Indonesia Stock Exchange, by drawing attention to how Firm Size can moderate each effect. The study was carried out using quantitative approaches along with tools for verification and description analysis. The study employed secondary data gathered from the 2015–2022 annual financial statements of companies in the property and real estate subsector from the Indonesia Stock Exchange and the Company's official websites. Sampling was carried out using purposive random sampling technique, so that from the total population of 79 companies, but there were only 10 companies that were considered eligible for the sample. This study ensures that Total Asset Turn Over, Current Ratio, and Sales Growth have a significant effect on Return On Asset of property and real estate companies on the IDX 2015-2022, with a coefficient of determination of 50.7%. When moderated by Firm Size, the effect increases to 94.8%, emphasizing the importance of these factors and the significant role of Firm Size in increasing profitability